Copper transporter 1, metallothionein and glutathione reductase genes are differentially expressed in tissues of sea bream (Sparus aurata) after exposure to dietary or waterborne copper - Minghetti, Matteo; Leaver, Michael; Carpene, Emilio; George, Stephen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2008)
The high affinity copper transporter 1 (Ctr1), metallothionein (MT) and glutathione reductase (GR) are essential for copper uptake, sequestration and defense respectively. Following rearing on a normal commercial diet (12.6±0.2 mgKg-1Cu), sea bream were fed an experimental control diet lacking mineral mix (7.7±0.3 mgKg-1Cu), an experimental diet enhanced with Cu (135±4 mgKg-1 Cu) or an experimental diet (7.7±0.3 mgKg-1Cu) while exposed to Cu in water (0.294±0.013mgL-1). Fish were sampled at 0, 15 and 30 d after exposures. Fish fed the Cu-enhanced experimental diet showed lower levels of expression of Ctr1 in the intestine and liver compared to fish fed control experimental diets, whilst Ctr1 expression in the gill and kidney was unaffected by excess dietary Cu exposure. Waterborne Cu-exposure increased Ctr1 mRNA levels in the intestine and the kidney compared to experimental controls. Excess dietary Cu exposure had no effect on levels of metallothionein (MT) mRNA, and the only effect of dietary excess Cu on glutathione reductase (GR) mRNA was a decrease in the intestine. Both MT mRNA and GR were increased in the liver and gill after waterborne Cu exposure, compared to levels in fish fed experimental control low Cu diets. Thus, Ctr1, MT and GR mRNA expression in response to excess Cu is dependent on the route of exposure. Furthermore, the tissue expression profile of sea bream Ctr1 is consistent with the known physiology of copper exposure in fish and indicates a role both in essential copper uptake and in avoidance of excess dietary and waterborne copper influx.